Assisted Reproductive Technologies (ART) in a model of fertility choice - Helmut Rainer; Geethanjali Selvaretnam; David Ulph (University of Essex, Institute for Social and Economic Research (ISER), 2008)
This paper provides a simple theoretical framework to discuss the relationship between assisted reproductive technologies and the microeconomics of fertility choice. Individuals make choices of education and work along with decisions about whether and when to have children. Decisions regarding fertility are influenced by policy and labor market factors that affect the earnings opportunities of mothers and the costs of raising children. We show how observed differences in these economic factors across countries explain observed different fertility and childbearing age patterns. We then use the model to predict behavioral responses to biomedical improvements in assisted reproductive technologies, and hence the impact of these technologies on fertility.
Keywords: 330